2001
DOI: 10.1021/ol016703i
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stereoselective Syntheses of Five- and Seven-Membered Ring Heterocycles from Ylides Generated by Catalytic Reactions of Styryldiazoacetates with Aldehydes and Imines

Abstract: [reaction--see text] Styryldiazoacetates are effective reactants for ylide formation that results in the formation of dihydropyrroles and dihydroazepines with high stereocontrol and in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…Doyle et al [591] studied the reaction of the PFBA with methyl styryldiazoacetate catalysed with Rh 2 (OAc) 4 in CH 2 Cl 2 , yielded 47% oxirane and 53% 4,5-dihydrofuran derivative (Scheme 65). Analogous oxirane cycles were described by Filler and Rao [592].…”
Section: Other Chemical Reactions Of Aldehydic Function Of Pentafluormentioning
confidence: 99%
“…Doyle et al [591] studied the reaction of the PFBA with methyl styryldiazoacetate catalysed with Rh 2 (OAc) 4 in CH 2 Cl 2 , yielded 47% oxirane and 53% 4,5-dihydrofuran derivative (Scheme 65). Analogous oxirane cycles were described by Filler and Rao [592].…”
Section: Other Chemical Reactions Of Aldehydic Function Of Pentafluormentioning
confidence: 99%
“…Imines and their derivatives are versatile intermediates in organic synthesis [1], in particular for the preparation of heterocycles [2], anti-inflammatory agents [3], non-natural aminoacids [4], liquid crystalline materials [5], and anticancer agents [6].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first preparation of imines was reported by Schiff more than a century ago [7], a variety of methods/ systems for the synthesis of imines have been described, such as ZnCl 2 [8], TiCl 4 [9], MgSO 4 -PPTS [10], alumina [11], Ti(OR) 4 [12], Er(OTf) 3 [13], MgSO 4 [14], MgClO 4 [15], P 2 O 5 /Al 2 O 3 [16], CuSO 4 [17], and NaHCO 3 [18], in which metal species act as Lewis acids to activate the carbonyl group as well as facilitating the removal of water. In the past few years, with the development of experimental techniques, some innovations were reported, including solid-state synthesis [19], solvent-free/clay/microwave irradiation [20], water suspension medium [21], solvent/ reflux [22], infrared irradiation/no solvent [23], K-10/ microwave [24], silica/ultrasound irradiation [25], NaH-SO 4 ÁSiO 2 /microwave/solvent-free [26], dirhodium Caprolactamate [27], [bmim]BF 4 /molecular sieves [28] and et al The methods/systems aforementioned showed some disadvantages such as the requirements of high reaction temperatures, prolonged reaction periods, moisture sensitive catalysts, large quantities of aromatic solvents, costly dehydrating reagents/catalysts and special instruments [25].…”
Section: Introductionmentioning
confidence: 99%
“…[20] The most pronounced effect was found for diazoacetates functionalized with electron-donating groups, for example, vinyl and aryl. It has been shown independently by the groups of Davies [21] and Doyle [22] that Rh-cata- Table 2. 1,3-Dipolar cycloaddition to benzylimines.…”
Section: Resultsmentioning
confidence: 99%